The role of serum and urinary carbohydrate antigen 19-9 in predicting renal injury associated with ureteral stone. (25th November 2016) - Amini, Erfan; Pishgar, Farhad; Hojjat, Asal; Soleimani, Mohammad; Asgari, Majid Ali; Kajbafzadeh, Abdol-Mohammad
Abstract: This study was designed to evaluate the role of urinary and serum carbohydrate antigen 19-9 (CA19-9) as a biomarker in the assessment of patients with ureteral stone. A total of 38 patients with ureteral stone and hydronephrosis who underwent transurethral lithotripsy (TUL) (Group A) and 24 age-matched healthy controls (Group B) were evaluated in this study. Urinary and serum CA19-9 concentrations were measured in group A patients before TUL as well as 4 and 8 weeks following the operation. Urinary and serum CA19-9 concentrations were also measured in group B participants. Median concentration of urinary and serum CA19-9 was 34.0 and 15.0 kU/L in group A patients and 16.1 and 5.3 kU/L in group B, respectively ( p <  0.001). Medians of CA19-9 concentration in urine and serum reduced to 12.5 and 4.5 kU/L 8 weeks after TUL ( p <  0.001). Following successful TUL and hydronephrosis resolution, a significant decline was detected in serum and urinary CA19-9. We also noted that duration of ureteral obstruction was associated with serum and urinary CA19-9 concentrations, suggesting the potential role of this marker in predicting renal damage associated with urinary tract obstruction and determining the appropriate timing of interventions.